ANALISIS HISTORIS PENERAPAN MOBILISASI DANA ZAKAT INFAK DAN SEDEKAH OLEH NEGARA - Hermawan, Ari (Jurnal Fakultas Ilmu Keislaman UNISA Kuningan, 2025)
This study examines the historical development of zakat mobilization in Indonesia, particularly the involvement of the state in the management of zakat, infak, and sedekah through the Badan Amil Zakat Nasional (BAZNAS). The research shows a significant shift from zakat being an individual religious duty to becoming an integral part of the state's fiscal policy. Despite the potential of state involvement, challenges in implementing zakat collection through civil servants (ASN) remain, particularly with issues related to automatic payroll deductions and differing views on zakat profesi (income tax). The study finds that while the state’s role in zakat management has become a strategy for social welfare, it also raises debates regarding religious obligations and implementation across various regions. The study concludes that despite zakat’s transformation into a state tool for fiscal policy, the ongoing discussion on its legitimacy and application highlights the need for a middle ground acceptable to both religious scholars and society. Future research could explore the role of non-state institutions in zakat management and their interaction with state-run bodies like BAZNAS.